Conceptualizations of "results" in Swedish policy for development cooperation from the 1960s to the 2000s - Brolin, Therese (Bulletin of Geography. Socio-economic Series, 2016)
Over the last few decades there has been an increased focus on results within development cooperation, and there has been an intense debate regarding the possible success or failures of development efforts. However, there is no general agreement on what a development result is, or why and whose development results should be reported. The understanding of what a development result entails has also shifted over time. This article aims to contribute to the current debate on development results by exploring how one donor, Sweden, historically has conceptualized development results in its policies and strategies on development cooperation. A review of all policies and general strategies on Swedish development cooperation published between 1962 and 2013, reveals that there has been a shift in how results are conceptualized: from being a mere instrument for supporting partner countries in pursuing more effective development policies and interventions, reporting of development results has become one of the main strategic tools for pursuing a Swedish development cooperation.